INITIAL LITERACY VIA SYSTEMATIC TEACHING FOR CHILDREN WITH EXTERNALIZING BEHAVIORS - Guidugli, Priscila Meireles [UNESP]; Almeida-Verdu, Ana Claudia Moreira [UNESP] (FapUNIFESP (SciELO), 2021)
Externalizing behaviors such as throwing tantrums and aggression are often competing with academic learning. The higher frequency of one behavior over another may indicate flaws in the planning of teaching conditions. It was verified if three boys, between nine and 10 years old, with externalizing behaviors measured by the TRF instrument and not literate, would learn to read and write when exposed to ALEPP (LRWSS - Learning to Read and Write in Small Steps). Teaching program according to equivalence-based instruction and operational approach to symbolic behaviors, with four units, divided into 17 teaching steps, preceded and succeeded by tests. There was no intervention on externalizing behaviors. The results showed more than 80% of correct responses in reading and writing. Future research should verify the replicability of these results with more participants and if the acquisition of academic repertoires would affect the frequency of externalizing behaviors, considering the teacher’s abilities to reinforce academic repertoires at the expense of externalizing behaviors.
Alfabetización inicial vía enseñanza sistemática para niños con comportamientos externalizantes
Alfabetização inicial via ensino sistemático para crianças com comportamientos externalizantes
Keywords: behavior problems; school learning; teaching